2016
DOI: 10.21037/jtd.2016.02.51
|View full text |Cite
|
Sign up to set email alerts
|

Impact of attenuated plaques on TIMI grade flow and clinical outcomes of coronary artery disease patients: a systematic review and meta analysis

Abstract: Background: Plaques with a large necrotic core or lipid pool and thin-cap fibroatheroma manifest as attenuated plaques on intravascular ultrasound (IVUS). Their impact on TIMI grade flow and clinical outcomes remains undefined. We performed a systematic review and meta-analysis to summarize the association between attenuated plaque and distal embolization and clinical outcomes of coronary artery disease (CAD) from pooled data of published eligible cohort studies. Methods:We searched the literature on TIMI grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Tanaka et al proved that coronary microembolization is one of the main causes of slow- or no-reflow phenomena [ 16 ]. Jia et al, with the use of IVUS found that the presence of low-attenuation plaques was associated with more than four-fold increase in the risk of TIMI 0–2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka et al proved that coronary microembolization is one of the main causes of slow- or no-reflow phenomena [ 16 ]. Jia et al, with the use of IVUS found that the presence of low-attenuation plaques was associated with more than four-fold increase in the risk of TIMI 0–2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As is known, the production of superoxide anion radicals is essential for an aerobic organism. These pro-oxidative markers act as signaling molecules in various processes such as aging and apoptosis [35]. In addition, in many chronic diseases such as diabetes and ischemic vascular disease, superoxide anion radicals are important biomolecules that can alter physiological function [35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, NO is a potent endogenous vasodilator and also has the effect of inhibiting platelet aggregation and vascular smooth muscle cell proliferation ( Tettey et al, 2021 ). Studies have shown that impairment of endothelial function is closely related to the occurrence of CSF, and the degree of impairment of endothelial function is negatively correlated with the plasma NO level, but positively correlated with the ET-1 level ( Ma et al, 2013 ; Jia et al, 2016 ). Reactive oxygen species and oxidative stress are the main pathological mechanisms of endothelial dysfunction ( Ungvari et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%